The role of carbonate factories and sea water chemistry on basin‐wide ramp to high‐relief carbonate platform evolution: Triassic, Nanpanjiang Basin, South China. (12th September 2021) - Lehrmann, Daniel J.; Stepchinski, Leanne M.; Wolf, Hannah E.; Li, Liangzi; Li, Xiaowei; Minzoni, Marcello; Yu, Meiyi; Payne, Jonathan L.
Abstract: The end‐Permian extinction and its aftermath altered carbonate factories globally for millions of years, but its impact on platform geometries remains poorly understood. Here, the evolution in architecture and composition of two exceptionally exposed platforms in the Nanpanjiang Basin are constrained and compared with geochemical proxies to evaluate controls on platform geometries. Geochemical proxies indicate elevated siliciclastic and nutrient fluxes in the basal Triassic, at the Induan—Olenekian boundary and in the uppermost Olenekian. Cerium/Ce* shifts from high Ce/Ce* values and a lack of Ce anomaly indicating anoxia during the Lower Triassic to a negative Ce anomaly indicating oxygenation in the latest Olenekian and Anisian. Uranium and Mo depletion represents widespread anoxia in the world's oceans in the Early Triassic with progressive oxygenation in the Anisian. Carbonate factories shifted from skeletal in the Late Permian to abiotic and microbial in the Early Triassic before returning to skeletal systems in the Middle Triassic, Anisian coincident with declining anoxia. Margin facies shifted to oolitic grainstone in the Early Triassic with development of giant ooids and extensive marine cements. Anisian margins, in contrast, are boundstone with a diverse skeletal component. The shift in platform architecture from ramp to steep, high‐relief, flat‐topped profiles is decoupled from carbonate compositions having occurred in the Olenekian prior to the onset of basin oxygenation and biotic stabilisation of the margins. A basin‐wide synchronous shift from ramp to high‐relief platforms points to a combination of high subsidence rate and basin starvation coupled with high rates of abiotic and microbial carbonate accumulation and marine cement stabilisation of oolitic margins as the primary causes for margin up‐building. High sea water carbonate saturation resulting from a lack of skeletal sinks for precipitation, and basin anoxia promoting an expanded depth of carbonate supersaturation, probably contributed to marine cement stabilisation of margins that stimulated the shift from ramp to high‐relief platform architecture. Abstract : Basin‐wide synchronous shift from ramp to high‐relief platforms in the Nanpanjiang Basin points to a combination of high subsidence rate and basin starvation coupled with high rates of abiotic and microbial carbonate accumulation and marine cement stabilisation of oolitic margins as the primary causes for margin up‐building. High sea water carbonate saturation resulting from a lack of skeletal sinks for precipitation, and basin following the end‐Permian mass extinction contributed to marine‐cement stabilisation of margins that stimulated the shift from ramp to high‐relief platform architecture.